Cardiovascular Effects of Treatment With the Ketone Body 3-Hydroxybutyrate in Chronic Heart Failure Patients. Issue 18 (30th April 2019) - Nielsen, Roni; Møller, Niels; Gormsen, Lars C.; Tolbod, Lars Poulsen; Hansson, Nils Henrik; Sorensen, Jens; Harms, Hendrik Johannes; Frøkiær, Jørgen; Eiskjaer, Hans; Jespersen, Nichlas Riise; Mellemkjaer, Søren; Lassen, Thomas Ravn; et al.
Abstract : Background: Myocardial utilization of 3-hydroxybutyrate (3-OHB) is increased in patients with heart failure and reduced ejection fraction (HFrEF). However, the cardiovascular effects of increased circulating plasma-3-OHB levels in these patients are unknown. Consequently, the authors' aim was to modulate circulating 3-OHB levels in HFrEF patients and evaluate: (1) changes in cardiac output (CO); (2) a potential dose-response relationship between 3-OHB levels and CO; (3) the impact on myocardial external energy efficiency (MEE) and oxygen consumption (MVO2 ); and (4) whether the cardiovascular response differed between HFrEF patients and age-matched volunteers. Methods: Study 1: 16 chronic HFrEF patients (left ventricular ejection fraction: 37±3%) were randomized in a crossover design to 3-hour of 3-OHB or placebo infusion. Patients were monitored invasively with a Swan-Ganz catheter and with echocardiography. Study 2: In a dose-response study, 8 HFrEF patients were examined at increasing 3-OHB infusion rates. Study 3 to 4: 10 HFrEF patients and 10 age-matched volunteers were randomized in a crossover design to 3-hour 3-OHB or placebo infusion. MEE and MVO2 were evaluated using 11C-acetate positron emission tomography. Results: 3-OHB infusion increased circulating levels of plasma 3-OHB from 0.4±0.3 to 3.3±0.4 mM ( P <0.001). CO rose by 2.0±0.2 L/min ( P <0.001) because of an increase in stroke volume of 20±2 mL ( P <0.001) and heart rate of 7±2 beats per minute (bpm) ( P <0.001). Left ventricular ejection fraction increased 8±1% ( P <0.001) numerically. There was a dose-response relationship with a significant CO increase of 0.3 L/min already at plasma-3-OHB levels of 0.7 mM ( P <0.001). 3-OHB increased MVO2 without altering MEE. The response to 3-OHB infusion in terms of MEE and CO did not differ between HFrEF patents and age-matched volunteers. Conclusions: 3-OHB has beneficial hemodynamic effects in HFrEF patients without impairing MEE. These beneficial effects are detectable in the physiological concentration range of circulating 3-OHB levels. The hemodynamic effects of 3-OHB were observed in both HFrEF patients and age-matched volunteers. 3-OHB may potentially constitute a novel treatment principle in HFrEF patients. Abstract : Supplemental Digital Content is available in the text.